A Study on Maximum Natural Ventilation for a Modern Single-Storey House by Using Simulation Software - Md Sali, Muhammad Nursyahmi; Saji, Nurdalila (Progress in Engineering Application and Technology, 2022)
In a nation like Malaysia, which is in a tropical climate, the issue of heat and humidity is one of the most critical challenges that must be addressed, particularly in residential buildings. Modern buildings are not planned with adequate cross-natural air circulation in mind but with an emphasis on aesthetics. Due to the warm climate, many homeowners choose air conditioning to reduce the indoor temperature, resulting in increased energy consumption. Hence, this study aims to analyse the different sizes of windows and then compare the result regarding their wind speed in the model. The location of this study is Bandar Melaka, Melaka, and the wind data collection was obtained from the Malaysian Meteorological Department (MetMalaysia). OnShape is the cloud-based software to construct the layout, and it is transferred to the simulation cloud-based software of SimScale to analyse the airflow in the house to gain thermal comfort. Four different sizes of windows are analysed following the standard size from MS1064:PART5:2001. The finding shows that the bigger size of the windows influenced the higher wind speed in the model. However, if the wind speed compares to the impact of occupants in MS 2680:2017, high wind speed in a building is not really suitable for thermal comfort.